Macro-Economic Policy in Australia, 1972 to 1976 - Jolley, Ainsley (London : Croom Helm, 1978)
This book outlines the development of Australian Government macro-economic policy in the years 1972 to 1976. The book also set out the main features of Government macro-economic policy in the context of how the economy appeared to be behaving at the time when the main policy decisions were made.
Includes bibliographical references and index.
hza 27/06/2018
Loans
Keywords: Economic policy; Australia